2021
DOI: 10.1038/s41598-021-85063-2
|View full text |Cite
|
Sign up to set email alerts
|

Possible limitations of dolphin echolocation: a simulation study based on a cross-modal matching experiment

Abstract: Dolphins use their biosonar to discriminate objects with different features through the returning echoes. Cross-modal matching experiments were conducted with a resident bottlenose dolphin (Tursiops aduncus). Four types of objects composed of different materials (water-filled PVC pipes, air-filled PVC pipes, foam ball arrays, and PVC pipes wrapped in closed-cell foam) were used in the experiments, respectively. The size and position of the objects remained the same in each case. The data collected in the exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…204,205 A number of studies have adopted CT scans and FEM to simulate sound generation and propagation in the heads of dolphins or whales, demonstrating how convergent sound beams can be generated and used to direct sound energy in a controlled manner, and also how sound reception can be directed through the lower jaw to the hearing organs. 206,207 Dible et al have even suggested that the teeth in the lower jaw can act as a periodic array of scattering elements generating angulardependent band gaps that can enhance the directional performance of the sensing process. 208 The emitted frequencies of the sounds used for echolocation are typically in the kHz range; e.g., bottlenose dolphins can produce directional, broadband clicks lasting less than a millisecond, centered between 40 and 130 kHz.…”
Section: Scorpion Sensingmentioning
confidence: 99%
“…204,205 A number of studies have adopted CT scans and FEM to simulate sound generation and propagation in the heads of dolphins or whales, demonstrating how convergent sound beams can be generated and used to direct sound energy in a controlled manner, and also how sound reception can be directed through the lower jaw to the hearing organs. 206,207 Dible et al have even suggested that the teeth in the lower jaw can act as a periodic array of scattering elements generating angulardependent band gaps that can enhance the directional performance of the sensing process. 208 The emitted frequencies of the sounds used for echolocation are typically in the kHz range; e.g., bottlenose dolphins can produce directional, broadband clicks lasting less than a millisecond, centered between 40 and 130 kHz.…”
Section: Scorpion Sensingmentioning
confidence: 99%
“…Generally referred to as medical husbandry or husbandry training, the integration of operant conditioning to all aspects of husbandry and veterinary care with an emphasis on positive reinforcement is transforming the field and enhancing animal welfare and wellbeing [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53]. By training the caretakers and the animals to perform medical behaviours, many high-risk procedures can be carried out without the need for chemical or manual restraint [53,54].…”
Section: Medical Husbandry-integrating Operant Conditioning In Preven...mentioning
confidence: 99%
“…The computational time of control system should be minimized to eliminate the time delay effects. The Dolphin Echolocation algorithm demonstrated the fast and reliable optimization in comparison with other algorithms [17][18][19][20]. Kaveh and Farhoudi introduced a novel optimization algorithm, which was inspired from Dolphin echolocation in nature [21].…”
Section: Dolphin Echolocation Optimization Algorithm (De)mentioning
confidence: 99%
“…The computational time of control system should be minimized to eliminate the time delay effects. The Dolphin Echolocation algorithm demonstrated the fast and reliable optimization in comparison with other algorithms, such as genetic algorithm, particle swarm optimization, ant colony optimization in several researches [17][18][19][20]. The dolphin echolocation optimization algorithm was proposed based on the process of foraging preys utilizing echolocation in dolphins, which was familiar to discovering the optimal solution on a search space.…”
Section: Introductionmentioning
confidence: 99%